The inner program for the care and use of laboratory animals in biomedical, research and pharmaceutical institutions - Fernández Hernández, Jorge; Heuze de Icaza, Yvonne Michelle (Acta Bioethica, 2007)
This paper has as goal to analyze the ethics of the care and use of experimental biomodels known as "laboratory animals". It does not pretend to establish a unique model, but to describe the items to be considered by institutions which produce, maintain and use laboratory animals for academic and/or productive purposes, in order to establish an institutional program for the care and use of animals with the highest scientist, technical and ethical standards. In the same way, it reviews the public perception on the topic and the ethical concerns about the use of laboratory animals in scientific reseach.